1978
DOI: 10.1128/aem.35.1.210-213.1978
|View full text |Cite
|
Sign up to set email alerts
|

Pectolytic enzymes in Rhizobium

Abstract: A sensitive pectin agar plate assay was used to demonstrate low levels of pectolytic enzymes in infective and noninfective strains of Rhizobium. The possible relation of this characteristic to legume infection is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
5

Year Published

1982
1982
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(23 citation statements)
references
References 1 publication
0
18
0
5
Order By: Relevance
“…The use of nutrients from recalcitrant pollen cell walls could very well give this, or other candidate pectin digesters, an advantage in the gut environment. Pectin-degrading enzyme activities have indeed been detected from several Rhizobiales bacteria (Hubbell et al 1978;Mateos et al 1992;Fauvart et al 2009), further suggesting the plausibility of such a role.…”
Section: Causes and Consequences Of Diet-induced Plasticitymentioning
confidence: 90%
“…The use of nutrients from recalcitrant pollen cell walls could very well give this, or other candidate pectin digesters, an advantage in the gut environment. Pectin-degrading enzyme activities have indeed been detected from several Rhizobiales bacteria (Hubbell et al 1978;Mateos et al 1992;Fauvart et al 2009), further suggesting the plausibility of such a role.…”
Section: Causes and Consequences Of Diet-induced Plasticitymentioning
confidence: 90%
“…Alternatively, some of the bacterial symbionts may produce very small amounts of enzymes degrading the polymers found in the plant roots. Among such activities, Hubbell et al [49] proposed that temperate strains of Rhizobium used low levels of pectolytic enzymes in the infection process but did not identify whether lyases were involved. A later study by Mateos et al [78] indicated that polypectate-degrading enzymes were cell-bound rather than extracellular and were constitutive, but as a reducing sugar assay for the products was used, no indication of the mode of action was obtained.…”
Section: Role In Plant~bacterium Interactions?mentioning
confidence: 99%
“…Evidence against the involvement of pectolytic enzymes produced by the plant in the infection process has been accumulated (Lillich & Elkan 1968;McMillan & Cooke 1969;Solheim & Raa 1971). On the other hand, the ability of Rhizobium to produce cell wall degrading enzymes (Hubbell et al 1978;Martinez-Molina et al 1979), together with the results of an electron microscopy study of sites of infection made by Callaham (1979) that showed cell wall erosion or dissolution surrounding the attached bacteria, strongly support the hypothesis that the cell wall degrading enzymes implicated are of a bacterial origin.…”
Section: Resultsmentioning
confidence: 93%
“…The implication of hydrolytic enzymes in the active penetration of the plant cell wall by pathogenic micro-organisms has been well established (Albersheim et al 1969). The low levels of pectolytic (Hubbell et al 1978), cellulolytic and hemicellulolytic (Martinez-Molina et al 1979) enzyme activities found in Rhizobium, together with the reinterpretation of the infection process made by Cdllaham (1979)after a detailed electron microscopy study of sites of infection, strongly support the importance of cell wall degrading enzymes produced by Rhizobium in the infection process. Low but highly localized enzymic activity at the sites of infection may permit an alteration of the plant cell wall responsible for the Rhizobium penetration.…”
mentioning
confidence: 99%